Decidability Issues for Petri Nets - Esparza, Javier; Nielsen, Mogens (BRICS Report Series, 1994)
This is a survey of some decidability results for Petri nets, covering the last three decades. The presentation is structured around decidability of specific properties, various behavioural equivalences and finally the model checking problem for temporal logics.